GAMBARAN PENGGUNAAN SARANG BURUNG WALET SEBAGAI TERAPI MIKRONUTRIENT DI INDONESIA: LITERATUR RIVIEW 2020 - Riski Annur; Annaas Budi Setyawan (Borneo Student Research (BSR), 2022)
Abstrak Tujuan penelitian : Untuk mengetahui gambaran penggunaan dompet sarang burung walet sebagai suplemen penambah nafsu makan di Indonesia pada tahun 2016-2020 Metodologi : : Metode penelitian ini adalah penelitian kepustakaan, yaitu penelitian yang berkaitan dengan metode pengumpulan data kepustakaan, atau penelitian yang objek penelitiannya melalui informasi kepustakaan (jurnal ilmiah). Results : The result of the research of the swallow nestquality depends on the type of species, feed type, andseason of the production of the lair. The productivity ofswiftlet nests is influenced by microhabitat. The microHabitat in question is the environment in which theswallow is resting, laying eggs, and raising children whohave been hatched. Micro Habitat is local so it can beeasily conditioned to the needs of 4 birds wallets. The content of Swallow nest as a micronutrient therapy. Macronutrient indicates that each part Dari para Walet Nest buurng memiliki Sangat Tinggi protein Konten di differences 60%.